Experimental investigation on Iroko wood used in shipbuilding. (January 2017) - Bucci, V; Corigliano, P; Crupi, V; Epasto, G; Guglielmino, E; Marinò, A
The paper deals with investigations about mechanical properties of Iroko, a hardwood species used for structures in shipbuilding as glued laminated timber. Experimental tests have been carried out to assess strength, stiffness and density of Iroko in accordance with current EN Standards. All the results obtained by tensile and three-point bending tests, along with the statistical analyses performed to define the characteristics values of some mechanical properties, are reported in the paper. These values allowed to assign the strength class, reported in EN 338 Standard, to the investigated Iroko wood population. The experiments have taken into account both solid timber strips and scarf-jointed strips, in order to evaluate the influence of such a type of joint, which is widely used in wooden shipbuilding on strength and stiffness. Eventually, peculiar investigations have been carried out to analyse the failure mode of some test pieces through special experimental techniques: three-dimensional computed tomography and infrared thermography.